Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Untuk Meningkatkan Aktivitas Belajar Siswa Kelas IV SD Dwijendra Denpasar (Trapsila: Jurnal Pendidikan Dasar, 2021)
This study aimed at investigating the implementation of the snowball throwing cooperative learning model in improving the learning activities of fourth grade students of SD Dwijendra Denpasar. This type of research was Classroom Action Research (CAR) which consisted of 2 cycles. Each cycle consisted of planning, implementing actions, observing or evaluating and reflecting. The subjects of this study were 25 fourth grade students of SD Dwijendra Denpasar consisting of 8 male and 17 female students. The data on students' learning activities were obtained through observation with the assistance of observation sheet. The data analysis was facilitated by quantitative descriptive analysis technique. The results revealed that the implementation of Snowball Throwing cooperative learning model could improve the fourth grade students' learning activities at SD Dwijendra Denpasar. This could be seen from the average percentage of learning activities in the early reflection (pre-cycle) that was only 53.73%. Based on the results of study from cycle I to cycle II, the average percentage of students' learning activities in cycle I was 65.27% which was categorized as fairly active. After revising the action in cycle II, the average percentage of students' learning activities improved to 80.73%, and was categorized as active. Thus, the improvement of the average percentage on students' learning activities from cycle I to cycle II was 15.46%. Based on the results of the analysis, it could be concluded that the snowball throwing cooperative learning model could improve the learning activities of fourth grade students of SD Dwijendra Denpasar.